Vicente Fox presidential campaing and the model of propaganda in political communication - Adriana BORJAS BENAVENTE (América Latina Hoy, 2010)
<span style="font-family: SimonciniGaramond; color: #1c181b; font-size: 8.5pt; mso-fareast-language: ES; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: SimonciniGaramond; mso-ansi-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">The characteristics of political communication identified by Dominque Wolton can be used to analyse the electoral process of 1988 in Mexico, as public opinion and opinion began to emerge through the exchange between legitimate political actors. The main features of this exchange emerged and were consolidated during the 2000 presidential election campaign, coinciding with the typology developed by Gilles Achache regarding a model of propaganda. The objectives of the paper are to examine the electoral campaign of Vicente Fox of the <span style="font-family: SimonciniGaramond; color: #1c181b; font-size: 6.5pt; mso-fareast-language: ES; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: SimonciniGaramond; mso-ansi-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">PAN <span style="font-family: SimonciniGaramond; color: #1c181b; font-size: 8.5pt; mso-fareast-language: ES; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: SimonciniGaramond; mso-ansi-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">for the presidency in 2000, and to identify the differences that set it apart from the campaign of other candidates and from the traditional electoral behaviour of previous electoral processes, in order to demonstrate that through the use of techniques of political marketing in the public space, the Fox campaign introduced a new model of propaganda in political communication in Mexico.